ANALISIS KOMPARASI WIRELESS NETWORK PADA SIMULASI AIRLINK UBIQUITI DENGAN REAL HADWARE UBIQUITI - Ahmad Tantoni; Mohammad Taufan Asri Zaen (LPPM STMIK Lombok, 2018)
In conducting PtP or PtMP wireless signals, a simulation is needed with a design to determine the height of the tower and see the height of the surrounding buildings from the Access Point (site A) and Station (site B) to avoid the Line of Sight (LOS) and Fresnel Zone. Not only that, in designing the rt/rw.net network, it is also necessary to select devices and network simulation in order to estimate the results of the desired network performance and how much it costs. Problems occur when the network hardware has been installed and pointed from Site A to Site B to get unsatisfactory results according to previous simulations. This study is to determine the accuracy of the results of the ubiquiti simulation performance with the real hardware network Ubiquitous products. This is done because when sometimes simulateds, the expected results do not match the real estate. The research methodology used by PPDIOO Method is made by Cisco. Research at Brembuk.net Pancor, East Lombok with comparative analysis of wireless networks using simulation airlink.com ubiquiti and real hardware network ubiquitous products, carried out from site A to site B with a distance of approximately 1.47 kilometers. From the RX signal strength in the simulation is better than when using real hardware because the simulation produces a signal of -37.80 dBm while in the real hardware produces the signal -41.00 dBm. The total capacity of download & upload in real hardware is better than when using simulation because in real hardware it produces 137.54 Mbps while in simulation it produces 121.10 Mbps performance, and between airlink.ubnt.com using ubiquiti simulation and real hardware network ubiquiti products almost get the same results.